FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA INDIVIDUAL PADA BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - Wirawan, Bima Satya; Sadha Suardikha, I Made (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This research aimed to get the influence of the effectiveness to use of accounting information systems, beliefs, personal engineering capabilities and management support to individual performance. This study was conducted in 52 rural banks in Badung regency. The sample used in this study was a total of 147 respondents using saturated sample. Data analysis techniques used in this research is multiple linear regression analysis. These results of the research show that the effectiveness of the use of accounting information systems have positive and significant effect on individual performance. Confidence have positive and significant effect on individual performance. Personal technical ability have positive and significant effect on individual performance. Management support have positive and significant effect on individual performance.
Keywords: individual performance, the effectiveness of the use of SIA, confidence, personal technical capability, management support